Religious Moderation in Urban Indonesia: A Regional Development Approach - Putra, Ilham Mirzaya; Haikal, Muhammad Fachran; Priyantoro, Dian Eka (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study examines the dynamics of religious moderation in Bekasi, Medan, and Bandar Lampung through a regional development lens. By analyzing policies and activities in Bekasi, it identifies transferable factors for fostering religious harmony in other cities. The research addresses two key questions: (1) How do religious moderation and social interaction influence economic development? and (2) What role does social interaction play as a moderating variable in this relationship, particularly within regional development frameworks? Additionally, it explores the dynamics of religious moderation policies and initiatives in Medan, Bandar Lampung, and Bekasi. Employing a mixed-method sequential exploratory design, the study engaged millennials as the primary population and informants from six relevant agencies. Findings reveal that Bekasi’s implementable policies and community participation effectively sustain religious harmony, whereas Medan and Bandar Lampung require stronger approaches. The integration of religious moderation into regional development enhances harmonious social interactions and promotes inclusive, sustainable economic growth, offering a replicable model for other regions.